Environmental Exposure and Nonadherence with Medicines Directly Correlate with Exacerbations and Hospitalization for Asthma: A Population-Based Survey from UAE. (29th March 2012) - Mahboub, Bassam; Vats, Mayank; Afzal, Shahid; Sharif, Walid; Iqbal, Mohammed Nizam
Abstract : Acute severe exacerbation of asthma is directly related with the uncontrolled asthma including noncompliance with the medicines and exposure to the environmental factors. To our knowledge, none of the community-based study has explored the prevalence of asthma and other factors (namely, pattern of symptoms, environmental/occupational/housing/behavioral pattern/misperception about asthma, and educational factors) contributing to the exacerbation of asthma. We also studied the nonadherence issues related to the management of asthma in the United Arab Emirates (UAE). By using European Community Respiratory Health Survey (ECRHS) questionnaires and pooled data from AIRGNE (UAE) study, we aimed to determine the above-mentioned factors in the general population by means of a cross-sectional assessment of a random sample of 1, 229 participants of which 62.97% were male and 20.01% were UAE nationals, with a mean age (±SD) of 32.9 (±14.1) years. Prevalence of individual respiratory symptoms from the ECRHS questionnaire in all participants ranged from 8 to 10%, while those participants aged 20–44 years presented a lower prevalence in all symptoms (P < 0.05 ). Conclusion . Certain specific persistent environmental factor along with nonadherence to the controller medicines is a significant factor leading to uncontrolled asthma with consequent exacerbations, morbidity/mortality, and health care cost in UAE.